Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae) - Liu, Xiao-Tong; Jing, Jun; Xu, Yue; Liu, Yun-Fei; He, Zhu-Qing (Zootaxa, 2018)
Eight species of tree crickets are reviewed from China including Oecanthus antennalis, O. euryelytra, O. longicauda, O. similator, O. turanicus, O. zhengi, O. oceanicus He sp. nov. and Xabea levissima. Calling songs and COI genes of all species are compared. Keys to species are given by morphology and songs. New species is posited in Museum of Biology, East China Normal University (ECNU). The state of O. sinensis is discussed. O. latipennis Liu, Yin & Xia, 1994 is a junior homonym of O. latipennis Riley, 1881.